MENGUKUR LAPORAN KEUANGAN DENGAN CASH RATIO, RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) PADA KOPERASI WANITA (KOPWAN) SALIMA TUGUMULYO KABUPATEN MUSI RAWAS TAHUN 2016-2020 - Iwan, Iwan Sugianto; Fitriani, Fitriani; Haryati, Sani (JURNAL EKONOMI PERJUANGAN, 2023)
The purpose of this study is to: Know how the financial statement analysis of the Salima Women's Cooperative is viewed from the Cash Ratio in 2016-2020. Knowing how to analyze the financial statements of the Salima Women's Cooperative in terms of Return ON Assets (ROA) in 2016-2020. Knowing how to analyze the financial statements of the Salima Women's Cooperative in terms of Return On Equity (ROE) in 2016-2020. The data analysis method used in this research is quantitative descriptive analysis. The data collection techniques used in this study were observation, interviews and documentation. Analysis of the data used is the calculation of the liquidity ratio and profitability ratio with the classification guidelines of the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia, Number 06/Per/M.KUKM /V/2006. The results showed that: 1) Financial analysis on the liquidity ratio seen from the cash ratio was in bad condition. 2) Financial analysis on profitability ratios seen from Return On Assets is in fairly good condition. 3) Financial analysis of profitability ratios seen from Return ON Equity is in poor condition. Keywords: Financial Statements, Liquidity Ratio (Cash Ratio), Profitability Ratio (Return on assets, return on equity).